Effect of the thickness reduction on intergranular corrosion in an under–aged Al–Mg–Si–Cu alloy during cold–rolling. (September 2018) - Wang, Zhixiu; Zhu, Fan; Zheng, Kai; Jia, Jun; Wei, Yulong; Li, Hai; Huang, Lanping; Zheng, Ziqiao
Highlights: The IGC of the cold–rolled sheets increases firstly and then decreases with increasing the thickness reductions. The increased IGC results from the transformation of the initial low–angle grain boundaries to high–angle ones. The decreased IGC results from the small–sized grains formed at the high–angle grain boundaries. The difficulty for removing IGC correlates with the grain boundary plane orientations. Abstract: The effect of the thickness reduction on the intergranular corrosion (IGC) of under–aged Al–Mg–Si–Cu alloy sheets during cold–rolling is investigated. The accelerated corrosion test shows that the IGC susceptibility increases firstly and then decreases gradually with increasing the thickness reductions of the cold–rolled sheets. Microstructural observations indicate that the increased IGC susceptibility results from the transformation of the initial low–angle grain boundaries to high–angle ones, whereas its decrease correlates with the small–sized grains formed at the high–angle grain boundaries. Furthermore, the difficulty for removing IGC by cold–rolling increases gradually in the sequence of short–transverse, longitudinal–short and longitudinal–transverse grain boundary planes.